IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS MULTIKULTURAL DALAM PERSPEKTIF FILSAFAT PROGRESIVISME DI SMAN 2 SANGATTA UTARA - Faelasup, Faelasup (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research is motivated by the decline in the moral values ​​of the nation's children, especially school education (SLA). Many violations and social deviations are committed by school children (SLA). This research method is qualitative with primary data taken in the field, namely SMAN 2 Sangatta Utara. Analysis with character education theories, multicultural education and educational philosophical theories. The theoretical reference is used to analyze the data obtained in the field to reach the resulting conclusions. The results of research and discussion are as follows: 1) The implementation of character education that is integrated with intracurricular results is good but there are still difficulties in integrating the subject matter. 2) The implementation of character education integrated with extracurricular activities is very good, compulsory extracurricular or optional extracurricular activities.3) The application of multicultural education is very successful with extracurricular practices and habituation and becomes a very good school culture. 4) The perspective of progressivism philosophy is most widely used in the development of character education and multicultural education at SMAN 2 Sangatta Utara.